Allergen–Induced Sensory Neuroplasticity in Airways - Undem, Bradley J.; Hunter, Dawn D.; Liu, Mark; Haak-Frendscho, Mary; Oakragly, Angela; Fischer, Axel (International archives of allergy and immunology, 1999)
This study investigates the influence of allergic inflammation in airway sensory innervation. We conclude that allergic inflammation in the guinea pig leads to both an increase in excitability, as manifested by an increase in the mechanical sensitivity of the airway nerve endings, and an induction of substance P production in airway sensory neurons. The data are consistent with the hypothesis that the induction of substance P occurs in fast conducting nodose sensory neurons that were previously devoid of this neuropeptide. Thus, allergen challenge is associated with a phenotypic change in the airway tachykinergic innervation. We also provide evidence that nerve growth factor is a potentially important mediator for these effects, and that it is elevated in the bronchoalveolar lavage of asthmatic subjects.